Legal Accountability for Human Rights Violations in Indonesia - I Gede Kesuma Narendra (Universitas Bali Dwipa, 2025)
Serious human rights violations occurred in Indonesia despite the approval of several international human rights documents. Victims including their families and descendants have known suffering and loss. To this day, there are still many victims who have not received their rights. International law holds states accountable for the dignity of victims as individuals. This journal will look at approximately respecting victims' rights to effective and fair remedies and analyze the application of international human rights law in Indonesia in the field of respecting the rights of victims of gross human rights violations . The study was conducted using normative methods that collect and analyze information from various reading sources. The results showed that the right to know the truth (right to true), the right to justice (right before justice), the right to reparation and non-recidivism guarantees (guarantees not repeated) are one type of rights in the context of Transitional justice/Transitional justice must be returned to the victims. These rights are interrelated, so this should really be done. Concrete efforts have been made by Indonesia by establishing human rights courts to handle the cases of East Timor, Tanjung Priok and Abepura. Other attempts have been made in creating legal regulations. In fact, Indonesia only records and adjusts part of the rights. No current law encourages effective implementation, it is difficult to implement. So we must evaluate and review the existing legal provisions so that victims ' rights are fully recognized and easy to apply.